2016
DOI: 10.1136/emermed-2014-204493
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a simplified termination of resuscitation rule for adult traumatic cardiopulmonary arrest in the prehospital setting

Abstract: The simplified TOR rule appears to accurately predict non-survivors in adults with TCPA in the prehospital setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Most included studies ( n = 21) were published between 2016 and 2019 [ 27 – 47 ], and most of the 36 primary studies were carried out in either Europe ( n = 14) [ 2 , 3 , 6 , 19 – 21 , 28 , 32 , 33 , 35 , 36 , 40 , 44 , 46 ] or Asia ( n = 13) [ 22 , 25 , 26 , 30 , 31 , 34 , 37 39 , 41 , 43 , 45 , 47 ]. Almost all included studies were retrospective cohort studies ( n = 32) [ 1 3 , 16 18 , 20 38 , 40 44 , 46 , 47 ] and included both penetrating and blunt trauma cases ( n = 30) [ 1 3 , 16 , 17 , 19 – 21 , 23 25 , 27 , 28 , 30 36 , 40 47 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most included studies ( n = 21) were published between 2016 and 2019 [ 27 – 47 ], and most of the 36 primary studies were carried out in either Europe ( n = 14) [ 2 , 3 , 6 , 19 – 21 , 28 , 32 , 33 , 35 , 36 , 40 , 44 , 46 ] or Asia ( n = 13) [ 22 , 25 , 26 , 30 , 31 , 34 , 37 39 , 41 , 43 , 45 , 47 ]. Almost all included studies were retrospective cohort studies ( n = 32) [ 1 3 , 16 18 , 20 38 , 40 44 , 46 , 47 ] and included both penetrating and blunt trauma cases ( n = 30) [ 1 3 , 16 , 17 , 19 – 21 , 23 25 , 27 , 28 , 30 36 , 40 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…2 ). Within the 36 included studies, 13 studies reported neurological outcome as defined in the methods section [ 1 , 2 , 19 22 , 25 , 26 , 30 , 31 , 33 , 37 , 43 ]. Of all TCA survivors, a (pooled) favorable neurological outcome was observed in 43.5% of the TCA survival patients (95% CI 32.3–55.0).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We identified very-low-certainty evidence (downgraded for risk of bias, inconsistency, indirectness, and imprecision) from 12 nonrandomized studies. 48,51,56,57,65,66,75,76,79 , Between them these studies derived and internally validated 15 distinct TOR rules to predict death after arrival at hospital. Studies by Lee et al {Lee 2019 e134} and Yoon et al { Yoon 2019, 73} derived multiple TOR rules.…”
Section: Death In Hospitalmentioning
confidence: 99%
“… For this category 25 of the 29 articles could be retrieved and analyzed. Of the nine articles in the Clinical Protocol theme, there were two articles on non-invasive near-infrared spectroscopy (NIRS) [ 65 , 66 ], two on therapeutic hypothermia [ 67 , 68 ], and two on termination of resuscitation [ 69 , 70 ]. There was one article respectively on double sequential external defibrillation [ 71 ], extracorporeal CPR [ 72 ], and CPR induced consciousness [ 73 ].…”
Section: Resultsmentioning
confidence: 99%